Increased Violence Against Women in the Household Scope during the Pandemic - Chyntia Pradivtasari Utami; Putri Indah Maharani; Renanda Okta Saputra (Journal of Politics and Policy, 2021)
AbstractViolence against women, especially domestic violence, has increased during the Covid-19 pandemic. The occurrence of violence in household has various impacts on families, especially children. Women who are victims of violence will tend to keep their grief (psychologically and physically), they think that they have contributed to a crime, even though this is not the case. This research discusses violence against women, especially in the realm of household. The purpose of this study is to describe what kinds of violence can occur during a pandemic. Efforts to handle domestic violence cases are not easy to realize during a pandemic. The Large-Scale Social Restriction Policy (PSBB) that was implemented impeded the Ministry of Women's Empowerment and Child Protection (PPPA) from handling cases of violence against women. To reduce cases of violence against women requires cooperation and support from various partiesÂ Â Key word: Violence, Women, Household